2020
DOI: 10.1080/14992027.2020.1805804
|View full text |Cite
|
Sign up to set email alerts
|

Teleaudiology hearing aid fitting follow-up consultations for adults: single blinded crossover randomised control trial and cohort studies

Abstract: Objective: To evaluate and compare the effectiveness and quality of standard face-to-face and teleaudiology hearing aid fitting follow-up consultations and blended services for adult hearing aid users. Design and Study sample: Fifty-six participants were randomly allocated to two equal groups, with equal numbers of new and experienced users. One standard and one teleaudiology follow-up consultation were delivered by an audiologist, the latter assisted by a facilitator. The order was reversed for the second gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…What clinicians may be reporting are their own barriers to acquiring, installing and managing telehealth tools for their clients, reflective of the fact that there is no common platform for tele-audiology. It is also known that patient preference was typically for in-person service over telehealth services pre-COVID-19 (Eikelboom and Atlas 2005;Donelan et al 2019;Tao et al 2020). The findings from these questions were reinforced by responses to an open-ended question on what innovations and improvements audiologists would like to see, and confirm the findings of others (Saunders and Roughley 2020).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…What clinicians may be reporting are their own barriers to acquiring, installing and managing telehealth tools for their clients, reflective of the fact that there is no common platform for tele-audiology. It is also known that patient preference was typically for in-person service over telehealth services pre-COVID-19 (Eikelboom and Atlas 2005;Donelan et al 2019;Tao et al 2020). The findings from these questions were reinforced by responses to an open-ended question on what innovations and improvements audiologists would like to see, and confirm the findings of others (Saunders and Roughley 2020).…”
Section: Discussionmentioning
confidence: 78%
“…One-fifth of patients in a tinnitus treatment programme declined it being delivered remotely for reasons that included lack of access to devices, and lack of confidence of usefulness (Aazh, Swanepoel, and Moore 2021). Others report that patients are open to telehealth consultations, but retain a preference for face-to-face services (Eikelboom et al 2014;Eikelboom and Atlas 2005;Tao et al 2020). There was a strong recognition amongst audiologists that telehealth services can lead to better efficiency: less travel for clients or clinicians, more timely attention, and better overall access, as evidenced in the audiology (Saunders and Roughley 2020;Reginato and Ferrari 2014) and broader literature (Kokesh, Ferguson, and Patricoski et al 2011;Caffery, Farjian, and Smith 2016;Taylor et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The successful adoption of telehealth services will depend on patient and clinician's access to adequate technology as well as their willingness and ability to use it (Or and Karsh 2009;Gagnon et al 2003). Teleaudiology delivery has grown from diagnostic testing and information sharing, to the fitting and maintenance of hearing aids and cochlear implants (Tao 2020;Swanepoel de and Hall 2010;Bush et al 2016;Tao et al 2020). Audiological screening can be carried out with self-test procedures either using pure tone stimuli or speech/digits in noise via telephone or computer headphones (You et al 2020;Brown et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…61 Recent research has indicated that teleaudiology hearing device follow-up care (and blended care that combines face-to-face and remote care) is not considered to be different from standard (i.e., in-person) care. 62 Allison has completed two in-person visits (TRT evaluation, device delivery) and three teleaudiology visits (TRT teaching session, remote programming adjustment, 3-week follow-up). While her satisfaction was not measured formally, she expressed that she appreciated the opportunity to address programming issues, ask questions, and receive advice from her own home.…”
Section: Discussionmentioning
confidence: 99%